Pembayaran Upah dengan Penambahan Beban Kerja pada Posisi Pekerjaan Buruh Bengkel: Studi Penerapan Konsep Syariah di Padangsidimpuan - Qurtubi, Achmad Napis (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2023)
This research aims to analyze Islamic law concerning wage payments with added workloads, delve into relevant literature, evaluate field practices, and provide recommendations in line with Islamic principles to ensure fairness in employment relations and protect workers' rights. The research methodology employs a qualitative approach with a case study involving surveys, observations, and interviews with workshop employers and laborers. Collected data are qualitatively analyzed to comprehend wage payment practices and added workload from the perspective of Islamic law. The research findings indicate that the majority of respondents give positive assessments of the examined practices. However, aspects such as the mechanism of workload addition, written agreements, and the impact of these practices on fairness and worker welfare require attention. In conclusion, the practice of wage payment with added workloads in Kota Padangsidimpuan needs further evaluation to align with Islamic legal principles. Recommendations include the necessity for clear regulations, a better understanding of Islamic law, and socialization among workshop employers and laborers to ensure these practices adhere to Islamic legal principles and safeguard workers' rights.